Aging in the sebaceous gland - Hou, Xiaoxiao; Wei, Ziyu; Zouboulis, Christos C; Ju, Qiang (Frontiers in Cell and Developmental Biology, 2022)
Sebaceous glands (SGs) originate from hair follicular stem cells and secrete lipids to lubricate the skin. The coordinated effects of intrinsic and extrinsic aging factors generate degradation of SGs at a late age. Senescence of SGs could be a mirror of the late aging of both the human body and skin. The procedure of SG aging goes over an initial SG hyperplasia at light-exposed skin areas to end with SG atrophy, decreased sebum secretion, and altered sebum composition, which is related to skin dryness, lack of brightness, xerosis, roughness, desquamation, and pruritus. During differentiation and aging of SGs, many signaling pathways, such as Wnt/β-catenin, c-Myc, aryl hydrocarbon receptor (AhR), and p53 pathways, are involved. Random processes lead to random cell and DNA damage due to the production of free radicals during the lifespan and neuroendocrine system alterations. Extrinsic factors include sunlight exposure (photoaging), environmental pollution, and cigarette smoking, which can directly activate signaling pathways, such as Wnt/β-catenin, Notch, AhR, and p53 pathways, and are probably associated with the de-differentiation and hyperplasia of SGs, or indirectly activate the abovementioned signaling pathways by elevating the inflammation level. The production of ROS during intrinsic SG aging is less, the signaling pathways are activated slowly and mildly, and sebocytes are still differentiated, yet terminal differentiation is not completed. With extrinsic factors, relevant signaling pathways are activated rapidly and fiercely, thus inhibiting the differentiation of progenitor sebocytes and even inducing the differentiation of progenitor sebocytes into keratinocytes. The management of SG aging is also mentioned.